The Influence of Investment Decisions, Dividend Policy and Capital Structure on Firm Value - Rusdiah Hasanuddin (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2021)
This study examines the effect of investment decisions, dividend policy, and capital structure on firm value. This study uses a sample of companies listed on the Indonesian Sharia Stock Index on the Indonesia Stock Exchange during the 2017-2019 period. The number of companies that became the population in this study was 421 companies. The sample of this study was 30 companies for three years; the total sample of the study was 90 financial statements and annual reports. The method used is the purposive sampling method. Hypothesis testing was used in this study using multiple linear regression analysis. This study indicates that dividend policy has a positive effect on firm value; meanwhile, investment decisions and capital structure do not affect firm value. Investment decisions proxied using Capital Expenditure to Book Value Assets (CPABVA) have an insignificant negative effect on firm value. Dividend policy which is proxied using the Dividend Payout Ratio (DPR), has a significant positive effect on firm value. Capital structure proxied by using the Debt to Equity Ratio (DER) has an insignificant negative effect on firm value. In this study, there are suggestions that companies should pay attention to the company's dividend policy ratio to increase company value, especially those listed on the Indonesian Sharia Stock Index; For investors when they want to invest, need to pay attention to the company's dividend policy ratio because the value of the company is significantly affected by this ratio; Further researchers can add research variables such as investment decisions and capital structure with different research objects because the results in this study do not affect the value of companies listed on the Sharia Stock Index.